Exploring the role of digital green marketing campaigns and environmental beliefs in shaping tourist behavior and revisit intentions in eco-tourism - Sanjaya, Daniel; Arief, Mts; Juli Setiadi, Nugroho; Heriyati, Pantri (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
Tourist behavior can have detrimental effects on eco-destinations, such as littering or starting fires. Digital green marketing campaigns and tourist beliefs, however, can influence visitor behavior. Using quantitative analysis, this study examines the role of digital green marketing campaigns and the visitors' beliefs about the environment on tourist pro-environmental behavior and their desire to revisit eco-destinations. The study was conducted by distributing an online survey to 306 respondents who have visited five ecotourism destinations in Indonesia. The acquired data was examined using the PLS-SEM (Partial Least Squares-Structural Equation Modeling) approach. The study found that digital green marketing campaign and tourists' beliefs about the environment positively impact tourists' environmental behavior and their desire to revisit eco-destinations. The tourism ecosystem, however, does not strengthen the relationship between tourist pro-environmental behavior and the revisit intention to eco-destinations. This study will add to the literature by examining the relationship between digital green marketing campaigns, visitors' environmental beliefs, pro-environmental behavior, tourism ecosystems, and revisiting intention to eco-destinations. The study will also provide Destination Marketing Organizations (DMOs) with specific recommendations to promote their eco-destinations, encouraging responsible travel and returning visits.